Digital business skills empowerment: Enhancing power aspects and economic independence of underprivileged orphans - Amanda, Fadia; Harisoesyanti, Kania Saraswati; Machdum, Sari Viciawati (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: This research is motivated by the condition of underprivileged orphans who are unable to pursue higher education and secure decent jobs due to the death of their parents and the poverty they experience. Meanwhile, the empowerment of underprivileged orphans, which is typically carried out by orphanages, is usually only done until they graduate from high school. Therefore, further empowerment is needed for underprivileged orphans to achieve their welfare. This research aims to explain the empowerment and aspects of power of underprivileged orphans developed through the ABC Jakarta program. Methods: This research uses a qualitative and descriptive approach conducted from March to June 2024. Data collection was carried out through in-depth interviews, participation observations, and literature studies involving twelve informants, namely four program implementers and eight students. Finding: The results of this research show that the empowerment of underprivileged orphans by ABC Jakarta, which focuses on digital business, consists of new student admissions, student orientation, education and training classes, service, internship, employment, and graduation. The process of empowering underprivileged orphans can be seen from increasing students' capacity, knowledge, skills, and learning motivation. A strength perspective is found in ABC Jakarta activities, which focus on developing the capacity and potential possessed by the underprivileged orphans as students. Empowerment is carried out so that the underprivileged orphans can have power. The aspects of power developed in this program are the power to make personal choices and determine life opportunities, define needs, think, access and utilize resources, and engage in economic activities. This power enables underprivileged orphans to improve their lives. Conclusion: The empowerment process in ABC Jakarta emphasizes the potential of underprivileged orphans so that they can have aspects of empowerment in order to change their life for the better through employment. Novelty/Originality of this article: The novelty/originality of this article lies in analyzing ABC Jakarta’s empowerment model, which uniquely focuses on developing digital business skills to enhance underprivileged orphans’ power, choices, and economic independence.